2016
DOI: 10.1002/acr.22652
|View full text |Cite
|
Sign up to set email alerts
|

Does Chondrocalcinosis Associate With a Distinct Radiographic Phenotype of Osteoarthritis in Knees and Hips? A Case–Control Study

Abstract: ObjectiveTo examine if knee chondrocalcinosis (CC), hip CC, or CC at distant joints associates with a distinct radiographic phenotype of osteoarthritis (OA) in knees or hips.MethodsWe conducted a case–control study using data from the Genetics of Osteoarthritis and Lifestyle (GOAL) study (n = 3,170). All participants of the GOAL study had radiographs of knees, hands, and pelvis, which have been scored for CC and for individual radiographic features of OA. For this study, cases had radiographic OA and CC, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(40 reference statements)
0
12
2
2
Order By: Relevance
“…In a more recent study, CC showed a significant correlation with the presence of knee osteophytes, but not with joint space narrowing . Additionally, another recent study reported that CC did not show any association with the radiographic findings of both osteophytes and joint space narrowing, associated only with attrition in knee OA . Although there are many reports that support the association between CC and knee OA, the marginal increase in MMP‐3 observed in the present study suggests that the development of degenerative changes in knee CC is likely to be low in magnitude.…”
Section: Discussioncontrasting
confidence: 62%
“…In a more recent study, CC showed a significant correlation with the presence of knee osteophytes, but not with joint space narrowing . Additionally, another recent study reported that CC did not show any association with the radiographic findings of both osteophytes and joint space narrowing, associated only with attrition in knee OA . Although there are many reports that support the association between CC and knee OA, the marginal increase in MMP‐3 observed in the present study suggests that the development of degenerative changes in knee CC is likely to be low in magnitude.…”
Section: Discussioncontrasting
confidence: 62%
“…The characteristics of the included studies are shown in Supplementary Table 1. Of the 29 studies that reported the study setting, nine included at least one subset of participants recruited from specific settings such as rheumatology and/or orthopedic clinics 11,27e31 , total knee replacement lists 27,32,33 , and a Caucasian sibling pairs database 34 ; all other studies were conducted in a community-based setting. A total of 22,546 persons were included in the 34 studies, with sample sizes ranging from 20 35 to 3494 36 persons (median ¼ 409, interquartile range (IQR) ¼ 198e715).…”
Section: Studies Includedmentioning
confidence: 99%
“…The mean age ranged from 50 to 73 years. Of the 19 studies that reported the distribution of the ROA severity among participants, eight included individuals within the whole spectrum of structural severity (Kellgren and Lawrence grade (KLG) 0e4) 10,11,15,16,36e39 , while five studies predominantly included persons with KLG 0 or 1 34,40e43 , four did not include early disease (i.e., limited to KLG 2 or over) 6,28e30 , and two predominantly included persons with severe ROA (KLG 3 or 4) 27,32 . Information regarding knee pain and/or function in the whole population at the time of subgrouping was not reported by the majority of studies (n ¼ 18).…”
Section: Studies Includedmentioning
confidence: 99%
“…cortical bone density, potentially mediated in part by dysregulated PPi metabolism (26). Moreover, in a study of severe symptomatic large joint OA, there was a milder imaging phenotype of hip OA linked with CPPD assessed by plain radiography (45), and this work needs validation in a larger cohort. There are challenges raised by the fact that advanced hip OA, with attendant cartilage loss, renders visualization of chondrocalcinosis more difficult.…”
Section: Unmet Needs In Cppd 1187mentioning
confidence: 99%